2016
DOI: 10.7753/ijsea0507.1006
|View full text |Cite
|
Sign up to set email alerts
|

Energy Loss Estimation and Flow Simulation in the skimming flow Regime of Stepped Spillways with Inclined Steps and End Sill: A Numerical Model

Abstract: Abstract:Energy dissipaters in dams consider as expensive structures; therefore, economic design of these structure are desirable.Stepped spillways can be use as energy dissipater to reduce the size and cost of the stilling basin. Hard experimental works, high-cost and time-consuming laboratory methods brought about some difficulties to determine the most-efficient design of the steps. This research deals with comparing the two-dimensional numerical simulation and experimental description in stepped spillways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Dimensionless parameter /ℎ was used to measure energy dissipation. The obtained results revealed that in the discharge of 30 / (discharge per unit width = 0.0225 2 / ), which indicates Nappe flow regime, the steps with simultaneous slope and sill (in which the ratio of m/h is less than 0.7) significantly increases energy dissipation [12].…”
Section: Literature Reviewmentioning
confidence: 82%
“…Dimensionless parameter /ℎ was used to measure energy dissipation. The obtained results revealed that in the discharge of 30 / (discharge per unit width = 0.0225 2 / ), which indicates Nappe flow regime, the steps with simultaneous slope and sill (in which the ratio of m/h is less than 0.7) significantly increases energy dissipation [12].…”
Section: Literature Reviewmentioning
confidence: 82%
“…Fluent is employed to solve Naiver-Stokes' equations. Many researchers used turbulent model (K-) to solve NaiverStokes' equations [9] [10] and compared their results with experimental works [11]. Since, this turbulent model is used to compute continuity and momentum equations in this study.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Also numerical studied by using Flow-3D to show the effect of the number of steps and drainage on top of the stepped spillway on the energy dissipation which showed the proof of the inverse relation between the discharge rate and the dissipation of energy and the great software simulation for different cases [4][5][6]. Based on the use of both FLUENT and V-Flow to modeling the unstable twodimensional flow over the stepped spillway, results obtained by the FLUENT program for the energy dissipation for the stepped spillway showed a reasonable agreement in results [7][8][9]. Also, artificial neural network (ANN) and the techniques of gene expression used for modeling the experimental data of nappe and skimming flow over stepped spillways, so the results obtained from these techniques were at a reliable level in the prediction of the energy dissipation [10].…”
Section: Introductionmentioning
confidence: 95%